Penerapan Sistem RPI (Retail Pro International) dalam meningkatkan kualitas layanan di PT. Transmarco Mong - Muhamad Akbar; Miffah Fauziah (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2020)
This study aims to determine the context of the Implementation of the Retail Pro International System at the Department of Merchandiser through (1) quality of the system, (2) quality of information, (3) quality of service, (4) quality of use, (5) user satisfaction, (6) usefulness, and are there any obstacles in the process of implementing the Pro Retail System in the Merchandiser Department. In this study the sample consisted of 6 informants, The informants consisted of 2 merchandisers, IT special retail pro, project management manager and pro retail vendors. This research uses triangulation method in qualitative writing. The author uses data analysis techniques of the Miles and Huberman model in which there are three activists in data analysis namely data reduction, data display, and conclusion drawing / verification. And on the conceptual model the writer uses DeLone and McLean Model.On service quality, information quality, service quality in implementing the Retail Pro System at the Merchandiser Department has not gone well because there are still some obstacles. For the intention of use, satisfaction of use, and usefulness is quite good in Implementing the Retail Pro System at the Merchandiser Department.